Effect of dynamic change in body mass index on the risk of hypertension: Results from the Rural Chinese Cohort Study. (1st July 2017) - Zhang, Ming; Zhao, Yang; Sun, Haohang; Luo, Xinping; Wang, Chongjian; Li, Linlin; Zhang, Lu; Wang, Bingyuan; Ren, Yongcheng; Zhou, Junmei; Han, Chengyi; Zhang, Hongyan; et al.
Abstract: Objectives: To examine the effect of change in body mass index (BMI) on incident hypertension by gender and age groups. Methods: A total of 10, 145 non-hypertensive participants 18–75 years old from rural areas in the middle of China were selected for this cohort study. Questionnaire interview and anthropometric and laboratory measurements were performed at baseline (during July to August 2007 and July to August 2008) and follow-up (during July to August 2013 and July to October 2014). Multiple logistic regression analysis was used to examine the relationship between change in BMI and incident hypertension. Results: During a mean follow-up of 6.03 ± 0.69 years, hypertension developed in 794 of 3986 men and 1184 of 6159 women. Both genders who were obese (BMI ≥ 28 kg/m 2 for Chinese people) at follow-up, regardless of their obesity status at baseline, showed greater risk of hypertension than those who were non-obese (BMI < 28 kg/m 2 ) at both baseline and follow-up. We found a dose-response relationship between change in BMI and incident hypertension. Risk of hypertension was markedly greater with a BMI gain of the highest quartile or more as compared with a BMI reduction of the lowest quartile or more, except for women 60–75 years old. Conclusions: Risk of hypertension was high for non-hypertensive people in rural China with stable obesity. BMI dynamic gain may be related to incident hypertension for men of all ages and young and middle-aged women.